2011
DOI: 10.1016/j.ygcen.2011.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Examining a pathway for hormone mediated maternal effects – Yolk testosterone affects androgen receptor expression and endogenous testosterone production in young chicks (Gallus gallus domesticus)

Abstract: Examining a pathway for hormone mediated maternal effects -Yolk testosterone affects androgen receptor expression and endogenous testosterone production in young chicks (Gallus gallus domesticus) Pfannkuche, K. A.; Gahr, M.; Weites, I. M.; Riedstra, Bernd; Wolf, C.; Groothuis, Ton

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 55 publications
3
35
0
Order By: Relevance
“…Lowered plasma testosterone concentrations following an in ovo manipulation of the yolk testosterone levels have been reported for two week old chickens (Pfannkuche et al, 2011), while two previous studies in quail respectively spotless starlings reported rather increased testosterone production post-hatching (Daisley et al, 2005;Müller et al, 2007). No differences were found in chicken embryos and in adult house sparrows measured in their fist spring (Partecke and Schwabl, 2008), when testosterone levels are typically elevated.…”
Section: Initial Differences Between Yt-and Yc-males Prior To Testostmentioning
confidence: 78%
See 3 more Smart Citations
“…Lowered plasma testosterone concentrations following an in ovo manipulation of the yolk testosterone levels have been reported for two week old chickens (Pfannkuche et al, 2011), while two previous studies in quail respectively spotless starlings reported rather increased testosterone production post-hatching (Daisley et al, 2005;Müller et al, 2007). No differences were found in chicken embryos and in adult house sparrows measured in their fist spring (Partecke and Schwabl, 2008), when testosterone levels are typically elevated.…”
Section: Initial Differences Between Yt-and Yc-males Prior To Testostmentioning
confidence: 78%
“…One pathway that has often been suggested is that yolk androgens alter the functioning of the hypothalamus-pituitarygonadal (HPG) axis, leading to changes in sex steroid production. This has indeed been shown, but the directions of these effects varied: a non-significant increase following yolk T injections in quail chicks (Daisley et al, 2005), a significant increase in spotless starling chicks (Müller et al, 2007), a decrease in chicks of the domestic chicken (Pfannkuche et al, 2011), while there were no effects in chicken embryos and adult house sparrows (Partecke and Schwabl, 2008) (see also Table 1). …”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Thus, endogenous testosterone regulation may have a crucial role in determining food intake and ultimately chick survival during a life stage where harsh competition by siblings can strongly increase the risk of starvation depending upon food availability. In birds, prenatal exposure to testosterone of maternal origin is can affect the density of androgen receptors in the hypothalamic region and the amount of endogenous T production in the first week after hatching (Pfannkuche et al, 2011). Thus, our study possibly also shed light on one of the mechanisms by which systematic variation over the laying sequence in the allocation of androgens of maternal origin can differentially affect the fitness of single brood mates (e.g.…”
Section: Discussionmentioning
confidence: 71%